Applying a Cognitive Neuroscience Perspective to Disruptive Behavior Disorders: Implications for Schools. Issue 1 (2nd January 2019) - Tyler, Patrick M.; White, Stuart F.; Thompson, Ronald W.; Blair, R. J. R.
ABSTRACT: A cognitive neuroscience perspective seeks to understand behavior, in this case disruptive behavior disorders (DBD), in terms of dysfunction in cognitive processes underpinned by neural processes. While this type of approach has clear implications for clinical mental health practice, it also has implications for school-based assessment and intervention with children and adolescents who have disruptive behavior and aggression. This review articulates a cognitive neuroscience account of DBD by discussing the neurocognitive dysfunction related to emotional empathy, threat sensitivity, reinforcement-based decision-making, and response inhibition. The potential implications for current and future classroom-based assessments and interventions for students with these deficits are discussed.